2005
DOI: 10.1007/s00192-005-1353-y
|View full text |Cite
|
Sign up to set email alerts
|

Does vaginal reconstructive surgery with or without vaginal hysterectomy or trachelectomy improve sexual well being? A prospective follow-up study

Abstract: Vaginal reconstructive surgery for pelvic organ prolapse has a positive effect on the sexual well being of the afflicted women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
2
14
0
2
Order By: Relevance
“…Studies reporting effect of surgical treatment of pelvic organ prolapse on sexual function come from several different countries and different cultures [22,26,27]. Both expectations form sexual relationships and a woman's comfort in expressing her sexual complaints vary by cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting effect of surgical treatment of pelvic organ prolapse on sexual function come from several different countries and different cultures [22,26,27]. Both expectations form sexual relationships and a woman's comfort in expressing her sexual complaints vary by cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, it has been shown that the sexual dysfunction rate was 20% after undergoing an anti-incontinence surgery. There are controversial studies regarding the effect of pelvic floor surgery on sexual functions; it may improve sexual functions, it may have no effect or there may be deterioration of sexual functions after surgery [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on surgical treatment of pelvic organ prolapse and sexual function have been conducted in several different countries and cultures 33-35. Sexual functions, including expectations for sexual relationships and sexual complaints, vary among cultures 33-35.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual functions, including expectations for sexual relationships and sexual complaints, vary among cultures 33-35. Accordingly, discrepancies in the results of earlier studies might originate from differences in demographic and clinical characteristics 33-35. Because of these differences, it is difficult to compare outcomes of different studies.…”
Section: Discussionmentioning
confidence: 99%